Applications, impacts and consequences of botulinum toxin usage in medicine - Weronika Kiełt; Julia Kozłowska; Gabriela Broniec; Barbara Wajdowicz; Aleksandra Kudła; Rozalia Czapiewska; Aleksandra Dziewulska; Aleksandra Wróbel; Laura Pacek; Klaudia Kowalska (Journal of Education, Health and Sport, 2024)
Introduction